Automatic determination of arsenate in drinking water by flow analysis with dual membrane-based separation. (15th June 2019) - Vera, Ruben; Zhang, Yanlin; Fontàs, Clàudia; Almeida, M. Inês G.S.; Anticó, Enriqueta; Cattrall, Robert W.; Kolev, Spas D.
Highlights: A gas-diffusion flow analysis method for As(V) in drinking water was developed. As(V) is preconcentrated by on-line separation using a polymer inclusion membrane. The membrane consists of PVDF-HFP as base polymer and Aliquat 336 as extractant. The method offers a limit of detection of 3 μg L −1 . As(V) was successfully determined in drinking water samples. Abstract: The sequential application of a polymer inclusion membrane (PIM), composed of poly(vinylidenefluoride-co-hexafluoropropylene) and the anionic extractant Aliquat 336, and a microporous polytetrafluoroethylene (PTFE) gas-permeable membrane was utilized for the first time to develop a flow analysis (FA) system, for the automatic determination of trace levels of arsenate (As(V)) in drinking water as arsine. The system incorporated a flow-through extraction cell for separation and preconcentration of arsenate and a gas-diffusion cell for the separation of arsine prior to its spectrophotometric determination based on the discoloration of a potassium permanganate solution. Under optimal conditions the FA system is characterized by a limit of detection of 3.0 μg L −1 As(V) and repeatability of 1.8% (n = 5, 25 μg L −1 As(V)) and 2.8% (n = 5, 50 μg L −1 As(V)). The newly developed FA method was successfully applied to the determination of arsenate in drinking water samples in the μg L −1 concentration range.